2016
DOI: 10.1136/bmjopen-2016-011828
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of cancers in Lahore, Pakistan, 2010–2012: a cross-sectional study

Abstract: ObjectivesTo estimate the population-level cancer estimates for the Lahore district, which is part of the Punjab Cancer Registry (PCR), Pakistan. The average population per year of Lahore was estimated at 9.8 million in 2010–2012.DesignA cross-sectional study.SettingThe Registry has 19 collaborating centres in Lahore that report their data to the Central Office located within a tertiary care cancer treatment facility in Lahore, Pakistan.ParticipantsPatients belonging to Lahore, of any age-group, and diagnosed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 6 publications
1
21
1
Order By: Relevance
“…The total number of malignancies recorded was 15 840, with 15 patients having double primaries. 4 This accounted for the difference in the numbers of patients and malignancies documented. 4 Of the 15 840 cases, 9069 (57.3%) were diagnosed in female and 6771 (42.7%) in male patients.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The total number of malignancies recorded was 15 840, with 15 patients having double primaries. 4 This accounted for the difference in the numbers of patients and malignancies documented. 4 Of the 15 840 cases, 9069 (57.3%) were diagnosed in female and 6771 (42.7%) in male patients.…”
Section: Resultsmentioning
confidence: 99%
“… 4 This accounted for the difference in the numbers of patients and malignancies documented. 4 Of the 15 840 cases, 9069 (57.3%) were diagnosed in female and 6771 (42.7%) in male patients. The female-to-male ratio among children was 0.46:1, in adolescents 0.48:1 and in adults 1.07:1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In case of South Asian countries especially Pakistan, Cancer prevalence ratio is gradually increasing. In Pakistan, between 2010-2012, data reported in Lahore indicated that about 15,840 patients were diagnosed with cancer including 43% males and 57% females [18]. In Liaquat National Hospital, cross sectional study conducted from 2011 to 2014 showed that 89 patients with CCL were recruited in which 69.7% were males and 30.3% were females; with age ranging between 35 -80 years.…”
Section: Introductionmentioning
confidence: 99%